DAMPAK PERUBAHAN STATUS BADAN USAHA CV MENJADI BADAN HUKUM PT TERHADAP PERJANJIAN KREDIT YANG SEDANG BERJALAN (STUDI PADA BANK BNI) - ADAM ADAM (PREMISE LAW JURNAL, 2016)
If the credit applied by the businessmen is big enough, the bank will ask for a certain amount of movable or unmovable collateral to meet the requirements for the credit extension, besides it can also change the form of business entity from unincorporated into incorporated enterprises.The change from comanditer company (CV) into a legal business entity such as limiuted liability company (PT) against the ongoing credit agreement shall begin with the renewal of credit agreement from previous debtor (CV) to current debtor (PT) resulting in a novation (debt renewal) with a number of additional requirements such as the addition of the collateral previously given. The collateral previously given on behalf of CV shall be cancelled with the agreement of Bank BNI and is transfered on behalf of PT as current/new debtor through a General Meeting of Stockholders. Keywords: Business Entity, Credit Agreement, Bank BNI